Product Profile and Marketing Channels used by Milk Processors in Karnal District of Haryana - Ashok Baindha , Gopal Sankhala , Man singh , Arvind Kumar , Sakainder Singh and Kuldeep Rai, (Indian Journal of Extension Education, 2017)
India is the largest milk producing country in the world; milk production is more than 127 million tons in a year. Out of theentire production, 55 per cent are consumed as fluid milk and rest 45 per cent are sent for industrial processing. In spite ofhaving largest milk production, India is a very minor player in the world market. Hence, there is a crucial need to developentrepreneurship in the field of milk processing. For the present study. Karnal district of Haryana was selected purposivelyfor its importance in milk production and processing due to presence of NDRI. The objective was to find out the productprofile and marketing channels used by dairy entrepreneurs. There were 41 registered milk processors and all theprocessors were interviewed for the study as respondents. It was observed that all the respondents process their availablemilk for butter, ghee, paneer and dahi. In addition with these major products, the respondents were also manufacturingice-cream, khoa, cheese, lassi, flavoured milk, etc. Paneer, butter, ghee and dahi were the major dairy products preferredand consumed by the people in the study area.